Postsynaptic and Spiking Activity of Pyramidal Cells, the Principal Neurons in the Rat Hippocampal CA1 Region, Does Not Control the Resultant BOLD Response: A Combined Electrophysiologic and fMRI Approach. Issue 4 (April 2015) - Scherf, Thomas; Angenstein, Frank
The specific role of postsynaptic activity for the generation of a functional magnetic resonance imaging (fMRI) response was determined by a simultaneous measurement of generated field excitatory postsynaptic potentials (fEPSPs) and blood oxygen level-dependent (BOLD) response in the rat hippocampal CA1 region during electrical stimulation of the contralateral CA3 region. The stimulation electrode was placed either in the left CA3a/b or CA3c, causing the preferentially basal or apical dendrites of the pyramidal cells in the right CA1 to be activated. Consecutive stimulations with low-intensity stimulation trains (i.e., 16 pulses for 8 seconds) resulted in clear postsynaptic responses of CA1 pyramidal cells, but in no significant BOLD responses. In contrast, consecutive high-intensity stimulation trains resulted in stronger postsynaptic responses that came along with minor (during stimulation of the left CA3a/b) or substantial (during stimulation of the left CA3c) spiking activity of the CA1 pyramidal cells, and resulted in the generation of significant BOLD responses in the left and right hippocampus. Correlating the electrophysiologic parameters of CA1 pyramidal cell activity (fEPSP and spiking activity) with the resultant BOLD response revealed no positive correlation. Consequently, postsynaptic activity of pyramidal cells, the most abundant neurons in the CA1, is not directly linked to the measured BOLD response.